Excellence in Postlicensure Interprofessional Palliative Care Education: Consensus Through a Delphi Survey. Issue 1 (February 2020) - Donesky, DorAnne; de Leon, Kathleen; Bailey, Amos; Doorenbos, Ardith; Fink, Regina; Hurd, Caroline; Ling, Perri; Kitko, Lisa
Abstract : An increasing number of palliative care educational programs strive to meet the workforce need for palliative care clinicians. This growth necessitates development of robust quality standards. The purpose of this Delphi consensus process was to describe high-quality postlicensure interprofessional palliative care education programs. The steering committee, composed of 6 faculty with experience implementing interprofessional palliative care educational programs, developed initial characteristics, definitions, and subcategories, which were refined through a series of 3 iterative Delphi surveys and a public presentation at a national palliative care meeting. More than 50 palliative care clinicians and educators representing multiple professions were invited to participate in the Delphi surveys; 20 completed round 1, 23 completed round 2, and 15 participants completed round 3. The final consensus included 6 characteristics with definitions, and both required and recommended subcategories for each characteristic. Identified characteristics include competencies, content, educational strategies, interprofessional focus, evaluation, and systems integration. This initial description of quality for postlicensure interprofessional palliative care education programs may be used by learners to guide program selection, new or existing program faculty for course development or quality improvement, or professional organizations to evaluate program quality in a program certification or quality award initiative.